Optimization of Heavy Key Composition of Distillate in Deisobutanizer Column Using Aspen Hysys with Flow Rate Reflux and Reboiler Temperature in Alkylation Unit at Company PEP - Aditya Dharmawan; Mahdi Suweleh; Sebhan Mulyawan (Scientific Contributions Oil and Gas, 2024)
The mass fraction of specific components is used to determine the product quality in distillation column process. Therefore, there is a need for sophisticated optimization strategies to identify ideal reflux flow rates and reboiler temperatures during operation. In distillation column, the most influential variables are reflux flow rate and reboiler temperature, which means the quantity and quality of distillate heavy fraction must remain below 3%. Simulation through Aspen Hysys identified optimal operating conditions at a 200 tons/day reflux flow rate and reboiler temperature of 72.58Â°C, decreasing from 3.38% to 2.19% by company standards. Following this optimization, an analysis of energy savings was conducted to compare actual field conditions and optimization at energy consumption levels of 2,989 kW and 1,688 kW, respectively. Energy savings were 1,301 kW in deisobutanizer column, downstream equipment, and depropanizer column feed pump. The energy required for deisobutanizer column pump was reduced from 0.907 kW to 0.88 kW after optimization, with a significant decrease in depropanizer column. The results showed an overall figure of the positive impact of optimizing operations in the central distillation column.